Penerapan Media Scrapbook (Diary) terhadap Keterampilan Menulis Siswa SMA Negeri 3 Pare-pare - Fauzan Djohar Difinubun; Nurmiah Muin; Rahmat Rahmat (Journal on Education, 2024)
Aplication of Scrapbook (Diary) Media to Biography Text Writing Skill of SMA N 3 Pare-pare students. Thesis. Indonesian Language and Literature Educarion, Faculty of Literature, Indonesian Muslim University. (Supervised by Nurmiah Muin and Rahmat). This study aimed to determine the effectiveness of the aplication of scrapbook (diary) media to biography text writing skill of Grade X Cerdas 4 SMA N 3 Pare-pare students. This research conducted with a total of 22 students and using a classroom action research approach carried out in 2 cycles. The instruments used in this study were observation sheets to measure students activity and writing skills tests to measure student’ wtiting skills in biography text learning. The results showed that the application of the aplication of scrapbook (diary) media effectively improved students’ biography text writing skills which was characterized by an increase in the percentage of students’ completeness in writing skills i.e from 27% in cycle I to 90% in cycle II. Students activity during the learning process also increased from cycle I first meeting was 37% and increased in the second meeting which was 50%, while in cycle II the first meeting was 63% and became 87% in the second meeting. This proved that students become more motivated and enthuastic during writing biography text learning by applying scrapbokk (diary) media. Based on the results of this study, it can be concluded that the application of scrapbook (diary) media to biography text writing skills learning is proven effective for improving grade X Cerdas 4 SMA N 3 Pare-pare students’ writing skills.